2014
DOI: 10.1186/2052-336x-12-8
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Zn(II) from electroplating effluent using yeast biofilm formed on gravels: batch and column studies

Abstract: BackgroundPresent study deals with the removal of Zn(II) ions from effluent using yeast biofilm formed on gravels.MethodsThe biofilm forming ability of Candida rugosa and Cryptococcus laurentii was evaluated using XTT (2,3-bis[2-methoxy-4-nitro-5-sulfophenyl]-2H-tetrazolium-5-carboxanilide) reduction assay and monitored by scanning electron microscopy (SEM), and Confocal laser scanning microscopy (CLSM). Copious amount of extracellular polymeric substances (EPS) produced by yeast species was quantified and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…With the pH increase, the cell surface becomes more negatively charged, resulting in the increase of the affinity to metal ions in cationic form. At pH 6.0, Candida rugosa biofilm showed maximum Zn(II) removal of 44%, whereas Cryptococcus laurentii biofilm removed 37% of Zn(II) [ 3 ]. Cu 2+ and Zn 2+ were effectively removed from aqueous solutions by S. cerevisiae crosslinked with formaldehyde at pH 5.3 and 6.0, respectively [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the pH increase, the cell surface becomes more negatively charged, resulting in the increase of the affinity to metal ions in cationic form. At pH 6.0, Candida rugosa biofilm showed maximum Zn(II) removal of 44%, whereas Cryptococcus laurentii biofilm removed 37% of Zn(II) [ 3 ]. Cu 2+ and Zn 2+ were effectively removed from aqueous solutions by S. cerevisiae crosslinked with formaldehyde at pH 5.3 and 6.0, respectively [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is an essential element involved in different metabolic processes and an important component of more than 200 enzymes [ 2 ]. At the same time, zinc compounds are widely used in different industrial processes, which often result in the release of zinc ions into the environment, at a concentration of physiological and ecological concern [ 3 ]. Wastewater released by different industrial processes (electroplating and surface finishing) and mining contain high concentrations of zinc among other metal ions [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Etracellular polysaccharides (EPS) play a significant role in cell adhesion and biofilm formation, which is closely related to colonization, mineral solubilizing ability, and protection against adverse environmental conditions (Basak et al, 2014;Marino et al, 2018;Yu et al, 2019). Gene clusters encoding for d-TDP-glucose pyrophosphorylase (rfbA), d-TDP-glucose 4,6dehydratase (rfbB), d-TDP-4-dehydrorhamnose 3,5-epimerase (rfbC), and d-TDP-4-dehydrorhamnose reductase (rfbD), which can convert glucose-1-phosphate to the EPS precursor d-TDP-rhamnose via a series of reactions, were found in all Metallosphaera genomes (Supplementary Figure S9).…”
Section: Adhesion and Motilitymentioning
confidence: 99%
“…These results are in agreement with those obtained by Padmavathy et al [21], who suggested that mannoproteins and glucans present on the cell wall were responsible for the sorption of Ni(II) ions. According to Basak et al [22] carboxyl, phosphate, sulfhydryl, hydroxyl and nitrogen-containing groups of yeast biomass surface participated in the removal of Zn(II) ion. Gerlach et al [27] have found that OH groups play the main role in iron ions binding.…”
Section: The Influence Of Ph On Metals Adsorptionmentioning
confidence: 99%